2002
DOI: 10.1590/s0100-879x2002001200004
|View full text |Cite
|
Sign up to set email alerts
|

Axonal pathfinding mechanisms at the cortical midline and in the development of the corpus callosum

Abstract: The corpus callosum is a large fiber tract that connects neurons in the right and left cerebral hemispheres. Agenesis of the corpus callosum (ACC) is associated with a large number of human syndromes but little is known about why ACC occurs. In most cases of ACC, callosal axons are able to grow toward the midline but are unable to cross it, continuing to grow into large swirls of axons known as Probst bundles. This phenotype suggests that in some cases ACC may be due to defects in axonal guidance at the midlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…The levels of fibronectin and laminin-1 present in astrocyte-conditioned medium were normalized for biglycan, a proteoglycan whose release by astrocytes is not affected by carbachol treatment. 4 It should be noticed that fibronectin levels were considerably higher than those of laminin, in agreement with a previous report (61).…”
Section: Resultssupporting
confidence: 91%
“…The levels of fibronectin and laminin-1 present in astrocyte-conditioned medium were normalized for biglycan, a proteoglycan whose release by astrocytes is not affected by carbachol treatment. 4 It should be noticed that fibronectin levels were considerably higher than those of laminin, in agreement with a previous report (61).…”
Section: Resultssupporting
confidence: 91%
“…Knockout studies in mice have demonstrated the involvement of a number of different genes in callosal development (reviewed in Richards, 2002;Richards et al, 2004b). These genes include guidance factors such as Slit2 (Bagri et al, 2002) and Netrin1 (Serafini et al, 1996), receptor molecules such as Robo (Richards et al, 2004a), DCC (Fazeli et al, 1997), and Npn1 (Gu et al, 2003), transcription factors such as Nfia (Shu et al, 2003b), Emx1 (Qiu et al, 1996;Yoshida et al, 1997), and Emx-2 (Pellegrini et al, 1996;Yoshida et al, 1997;Martins et al, 2004), as well as GAP43 (Shen et al, 2002).…”
Section: Expression Of Commissural Regulatory Genes In Developing Hummentioning
confidence: 99%
“…More dorsally, midline glial populations that make up the 'glial sling', 'glial wedge', and indusium griseum have all been implicated in midline crossing in the corpus callosum (Richards, 2002a;Shu et al, 2003a;Shu et al, 2003b;Shu et al, 2003c;Shu and Richards, 2001;Silver et al, 1982;Silver and Ogawa, 1983). Little is known about how midline cells influence the formation of the forebrain commissures.…”
Section: Introductionmentioning
confidence: 99%